Effectiveness of Gambir Solution (UncariagambirRoxb) on the Performances of Broiler Chickens were Infected by Escherichia coli. - Dora Villa Manik; Ma'ruf Tafsin; Armyn Hakim Daulay; Nurzainah Ginting; Hasnudi . (Universitas Sumatera Utara, 2018)
DORA VILLA MANIK, 2018.